Study on treatment of high COD fluorine-containing wastewater - TANG Xiangyang; WAN Jun; SUN Jianyang; YAN Yan (Gongye shui chuli)
To address the challenge of high COD fluorine-containing organic wastewater, a novel composite defluorinating agent, TS-F1, was developed. The defluorination performance of TS-F1 was compared with commonly used defluorinating agents, CaCl2 and AlCl3, under identical conditions for organic wastewater with different COD levels. The effects of TS-F1 dosage, reaction time, and reaction temperature on the removal of fluoride ions from fluorine-containing organic wastewater were also investigated. The results indicated that TS-F1 exhibited a higher defluorination rate compared to traditional CaCl2 and AlCl3 defluorinating agents, reducing the fluoride ion concentration from 50 mg/L to below 1.5 mg/L, which could meet the Class Ⅳ discharge standard of the Environmental Quality Standards for Surface Water (GB 3838-2002). Additionally, the defluorination rate increased with the increase of TS-F1 dosage, reaction time, and temperature. The study also found that COD significantly affected the defluorination rate. When COD≤60 mg/L, TS-F1 achieved optimal defluorination performance. For COD>60 mg/L, catalytic oxidation pretreatment was required to reduce COD to below 60 mg/L before defluorination. TS-F1 was an efficient and economical defluorinating agent. The study provided a reference for the treatment of high COD fluorine-containing organic wastewater in practical engineering.